Wave Hydrodynamics across Steep Platform Reefs: A Laboratory Study - Dinh Quang Cuong; Thieu Quang Tuan (Salehan Institute of Higher Education, 2022)
This paper presents a laboratory study on wave transmission across steep platform reefs, aiming at furthering knowledge of wave hydrodynamics and establishing empirical formulations of spectral wave parameters across the reef flat. The ultimate aim of this study is to determine the design wave load to design fixed offshore structures on coral reefs flat. The process of wave transmission across the underground coral strip with a large front slope has been studied on a physical model in the wave trough with nearly 300 experimental cases combined from 05 underground band models and many random wave scenarios and scenarios at different submerged depths. Experimental results show that the abrupt transition in depth from deep water ahead to relatively shallow water in the reef is responsible for the difference in the wave at the top of the strip compared to the wave on the normal beach, especially regarding the statistical distribution of the wave height. Breaking waves at the abrupt transition have deviated the wave height distribution curve from the deep-water (Rayleigh) theoretical distributions and even the existing shallow-water distributions, including the effect of breaking waves. Two sets of empirical formulations of the spectral wave parameters (Hm0 and Tm-1, 0) are eventually derived for the surf zone and the region behind the surf zone, respectively. These local wave parameters can be used as inputs to a wave height distribution model for determining other design characteristic wave heights on steep platform reefs. Doi: 10.28991/CEJ-2022-08-08-015 Full Text: PDF